Warpage Analysis of a Plastic Spur Gear Injection Molding. Issue 4 (2nd October 2017) - Chen, Dyi-Cheng; Huang, Chen-Kun; Lin, Jie-Wen
Abstract: The effect of various factors on the amount of warpage in an injection molded product was investigated and a plastic spur gear was used as an example. The research involved the design of a mold and die, computer-aided engineering, simulation analysis, and the determination of the plastic material and parameters. Simulation results were verified by experiment using the fabricated mold and die. Small warpage was determined using software, and the Taguchi and Response Surface Methods were used to determine the optimal parameter combinations. The optimum parameters were found to be: injection pressure, 105 MPa; packing pressure, 70 MPa; packing time, 19 s; mold temperature, 60 °C; and plastic temperature, 190 °C. The experiments were repeated, and the results were compared with the simulations to verify the reliability of the simulation results. Abstract :